STRATEGI KOMUNIKASI MELALUI METODE NLP (NEURO LINGUSTIC PROGRAMMING) DALAM PENYULUHAN PENYALAHGUNAAN NARKOBA KEPADA REMAJA DI DENPASAR SELATAN - Putu Soni Kurniawan; I Dewa Ayu Hendrawathi Putri; I Nyoman Alit Putrawan (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
The Drug abuse problems are increasingly apprehensive, the prevalence rate shows that from year to year the number of drug abusers tends to increase.  Data from the National Narcotics Board of the Republic of Indonesia states that in 2022 there will be approximately 5 million drug users in Indonesia. From the background of these problems, the researcher is interested in researching "Communication Strategy Through the NLP (Neuro Linguistic Programming) Method in Counseling Drug Abuse to Adolescents in South Denpasar, with the following problem formulation;  1) How is the application of the communication strategy through the NLP method in drug abuse counseling to adolescents in South Denpasar?  2) What are challenges in implementing communication strategies through the NLP method in drug abuse counseling to adolescents in South Denpasar?  3) What is the impact of implementing a communication strategy through the NLP method on drug abuse counseling to adolescents in South Denpasar? The theory used in this study is persuasive communication theory, symbolic interactionism theory and perception theory.  This study uses a qualitative approach.  Sources of data obtained through observation, interviews and documentation. The results of the study found 1) the application of communication strategies through the NLP method in drug abuse counseling to adolescents in South Denpasar, it can be seen that the strategies applied using anchoring, analogue marking, and building rapport techniques can be carried out well.  2) Challenges found were the large volume of counseling participants which tended to generate noise which made it difficult to create a conducive counseling atmosphere and the general lack of desire of the community to assist in counseling on drug abuse because it was felt that the subject did not provide feedback to the community.  3) the communication strategy implemented through the NLP method can be implemented properly.  Therefore, the strategies that have been implemented can be further developed and accelerate the development of communication strategies that are created by utilizing the SWOT analysis strategy so as to create an increasingly better communication strategy in counseling on drug abuse.